PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Mahasiswi Unisbank Pengguna Kosmetik Wardah) - Nona Nur Indah S., 15.05.51.0196; Liana, Lie (Students' Journal of Economic and Management, 2019)
This study aims to examine and analyze the effect of product quality, brand image, and price perception on purchasing decisions on wardah cosmetics. This study is a study on Unisbank female students wardah cosmetic users.The population of this research is Unisbank Student Wardah Cosmetic User. Sampling is done by using a purposive sampling method, namely students who buy and use wardah cosmetics. Determination of the sample is based on the opinion of Roscoe in Ferdinand (2006) stating that the sample size is as follows 3 x 25 = 75 samples. Based on this, the number of samples in the study were 100 respondents. The primary data collection method used is the questionnaire and interview method. Data were analyzed using test instruments, multiple linear regression, and model tests.The results showed that product quality has a negative effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, price perception has a positive and significant effect on purchasing decisions. The better the quality of the product, the lower the purchasing decision, the better the brand image, the higher the purchase decision, the better the perception of the price offered, the higher the purchase decision.Keywords: Product Quality, Brand Image, Price Perception and Purchasing Decision